Integrated single-cell chromatin and transcriptomic analyses of peripheral immune cells in patients with alopecia areata - Gay-Mimbrera, Jesus; Gómez-Arias, Pedro Jesús; Álvarez-Heredia, Pablo; Batista-Duharte, Alexander; Rivera-Ruiz, Irene; Aguilar-Luque, Macarena; Juan-Cencerrado, Miguel; Mochón-Jiménez, Carmen; Cebrián-García, Álvaro; Andújar-Pulido, Eloísa; Pérez-Alegre, Mónica; Pera, Alejandra; et al. (Frontiers in Immunology, 2025)
IntroductionAlopecia areata (AA) is an autoimmune disorder characterized by non-scarring hair loss ranging from mild, self-limiting episodes to severe and chronic forms. While prior research has primarily focused on lesional skin, the contribution of systemic immune cells remains underexplored.MethodsWe performed integrated single-cell RNA sequencing (scRNA-seq) and single-cell assay for transposase-accessible chromatin sequencing (scATAC-seq) on peripheral blood mononuclear cells (PBMCs) from patients with mild and severe AA, as well as healthy controls. A total of 32,453 high-quality cells were analyzed across 36 immune cell subtypes.ResultsIn AA patients, especially those with severe disease, we observed increased transcriptional heterogeneity, cytokine and chemokine pathway activation, and upregulation of antigen-presentation machinery enriched in TH1, TH2, and TH17 signatures. Chromatin accessibility profiling revealed 42,248 significant peaks with pronounced epigenetic remodeling in CD14+ monocytes, NK cells, and CD8+ T cells. Mild AA showed early immune regulatory failure, with elevated exhaustion markers in double-negative T cells and increased apoptosis in myeloid populations. Pseudotime and transcription factor analyses indicated altered differentiation trajectories, and inferred cell-cell communication networks highlighted monocytes, NK cells, and memory T cells as key signaling hubs.DiscussionOur results provide the first integrated single-cell chromatin and transcriptomic map of peripheral immune dysregulation in AA. These findings uncover systemic alterations associated with disease severity and identify candidate pathways for immune modulation and therapeutic targeting.